“It Makes Me Feel Like a Real Author”: Creating Multimodal, Digital Texts in an Elementary Writer’s Workshop - Moylan, Michael (Language and Literacy / Langue et littératie, 2025)
This study explored multimodal literacies as it pertained to the use of digital technologies to create multimodal, digital texts within the scope of writer’s workshop in a fifth-grade classroom. The research was conducted from the viewpoint of sociocultural theory, multiliteracies, and New Literacies as writing is a social practice and communication is multimodal. Analysis of six classroom observations, student interviews, a student focus group, and a teacher interview indicate using multimodal literacies: (a) fosters high levels of engagement, (b) enhances meaning-making, (c) fosters opportunities for collaboration, (d) provides opportunities for publishing of professional-looking books for an authentic audience, and (e) fosters writing skills and writer identity.